The Impact of Polychlorinated Biphenyls on the Development of Zebrafish (Danio rerio) - Megan Moma; Abi Lee; M. Brady Olson; Karin L. Lemkau; W. James Cooper (Biomedicines)
Polychlorinated biphenyls (PCBs) are a group of 209 highly stable molecules that were used extensively in industry. Although their commercial use ceased in 1979, they are still present in many aquatic ecosystems due to improper disposal, oceanic currents, atmospheric deposition, and hydrophobic nature. PCBs pose a significant and ongoing threat to the development and sustainability of aquatic organisms. In areas with PCB exposure high mortality rates of organisms inhabiting them are still seen today, posing a significant threat to local species. Zebrafish were exposed to a standard PCB mixture (Aroclor 1254) for the first 5 days post fertilization, as there is a gap in knowledge during this important developmental period for fish (i.e., organization of the body). This PCB mixture was formally available commercially and has a high prevalence in PCB-contaminated sites. We tested for the effects of PCB dosage (control (embryo water only; 0 mg/L), methanol (solvent control; 0 mg/L); PCB 1 (0.125 mg/L), PCB 2 (0.25 mg/L), PCB 3 (0.35 mg/L), and PCB 4 (0.40 mg/L)) on zebrafish survival, rate of metamorphosis, feeding efficiency, and growth. We found significant, dose-dependent effects of PCB exposure on mortality, feeding efficiency, and growth, but no clear effect of PCBs on the rate of zebrafish metamorphosis. We identified a concentration in which there were no observable effects (NOEC), PCB concentration above the NOEC had a significant impact on life-critical processes. This can further inform local management decisions in environments experiencing PCB contamination.